2011
DOI: 10.1371/journal.pone.0020092
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Bacillus subtilis Responding to Dissolved Oxygen in Adenosine Fermentation

Abstract: Dissolved oxygen (DO) is an important factor for adenosine fermentation. Our previous experiments have shown that low oxygen supply in the growth period was optimal for high adenosine yield. Herein, to better understand the link between oxygen supply and adenosine productivity in B. subtilis (ATCC21616), we sought to systematically explore the effect of DO on genetic regulation and metabolism through transcriptome analysis. The microarrays representing 4,106 genes were used to study temporal transcript profile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…Dissolved oxygen (DO) is an important factor that significantly influences metabolism, biomass synthesis, electron transport, ATP availability, peptide folding, and product yield of C . glutamicum when it expresses recombinant protein in a bioreactor [1, 14, 15], however, due to the complexity of the relationship between oxygen supplementation and fermentation production, increasing the DO level does not guarantee increased yield [15]. Zupke et al used quantitative estimates of intracellular flux to evaluate the effect of different DO concentrations on hybridoma cells in batch culture [16], and the result showed that physiological processes could be controlled through modulation of the DO level.…”
Section: Introductionmentioning
confidence: 99%
“…Dissolved oxygen (DO) is an important factor that significantly influences metabolism, biomass synthesis, electron transport, ATP availability, peptide folding, and product yield of C . glutamicum when it expresses recombinant protein in a bioreactor [1, 14, 15], however, due to the complexity of the relationship between oxygen supplementation and fermentation production, increasing the DO level does not guarantee increased yield [15]. Zupke et al used quantitative estimates of intracellular flux to evaluate the effect of different DO concentrations on hybridoma cells in batch culture [16], and the result showed that physiological processes could be controlled through modulation of the DO level.…”
Section: Introductionmentioning
confidence: 99%
“…The pfkA , pgk , and pykF genes, encoding the three rate‐limiting glycolytic enzymes phosphofructokinase, phosphoglycerate kinase, and pyruvate kinase, were up‐regulated by 3.5‐, 5.0‐, and 4.1‐fold, respectively. These changes clearly reflect increased ATP synthesis through substrate‐level phosphorylation and the increased production of precursors for biomass synthesis (Jouhten et al, 2008; Peng and Shimizu, 2003; Yu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We believe that the reduced precision rate of the expanded model is mostly an artifact resulted from the fact that the pathway models in MetaCyc are far from being complete. For example, we found that the following items are relevant with the target pathways but are not in MetaCyc, such as HemY (BSU10140) that is a peripheral membrane protein essential for protoheme IX synthesis [30] and may be related with the heme biosynthesis from uroporphyrinogen-III pathway in Table 1, ThiF (BSU11700) that is a thiamine biosynthesis protein [31] and may be related with the thiamin biosynthesis I pathway, and HisH (BSU34890), an imidazole glycerol phosphate synthase and HisZ (BSU34930) a histidyl-tRNA synthetase, both of which are involved in the histidine biosynthesis [32] and may be related with the histidine biosynthesis pathway, suggesting that CINPER could effectively recruit additional relevant genes into the target pathways, for which the additional experimental validation is needed.…”
Section: Resultsmentioning
confidence: 99%